In A, you are moving variables incorrectly.

**Quote:**

A) Solve for P2

E = A1P1 + A2P2 + A3P3

I get P2 = -E + A1P1 + A3P3/-A2

A2P2 = E - A1P1 - A3P3

Then to

\(P2 = \frac{E - A1P1 - A3P3}{A2}\)

It's easier to keep the variable that you are isolating as positive rather than moving it where it would be negative.

With this one: \(|\frac{x-4}{3}| + 2 = 4\) you do need to separate it into 2 equations, but I think this is where you made the mistake.

We have to simplify it first

\(|\frac{x-4}{3}| + 2 = 4\)

-2 from both sides

\(|\frac{x-4}{3}| = 2\)

now separate into 2 equations

\(\frac{x-4}{3} = 2\) and \(\frac{x-4}{3} = -2\)

First you get

\(x-4 = 6\); therefore x = 10

and \(x-4=-6\) +4 to both sides means x = -2

So the two answers for x are 10 and -2

These questions are not very detailed and are not like the real GMAT questions. Is each question posted in the same way you found it? If there is more context, please post that. Also, please state the source of the question when posting it.

_________________

------------------------------------

J Allen Morris

**I'm pretty sure I'm right, but then again, I'm just a guy with his head up his a$$.

GMAT Club Premium Membership - big benefits and savings